Uncertainty effect revisited using physical lottery format - Ondřej Rydval; Andreas Ortmann; Sasha Prokosheva; Ralph Hertwig (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We replicate three pricing tasks of Gneezy, List and Wu (2006) for which they document the so called uncertainty effect, namely that people value a binary lottery over non-monetary outcomes less than other people value the lottery's worse outcome. Unlike the authors who implement a verbal lottery description, we use a physical lottery format which rules out any misinterpretation of the lottery structure. Contrary to Gneezy, List and Wu, we systematically observe that subjects' willingness to pay for the lottery is significantly higher than other subjects' willingness to pay for the lottery's worse outcome.
Keywords: C81; C91; C93; D83; 330; Risky choice; framing; experiments; task ambiguity; Entscheidung bei Risiko; Framing; Glücksspiel; Willingness to pay; Test